The Curse of Beauty: Sexuality Exploitation towards Sales Promotion Girls’ Body Viewed from the Islamic Perspective - Fiqih Aisyatul Farokhah; Sri Kusumo Habsari; Mugijatna Mugijatna (Millati: Journal of Islamic Studies and Humanities, 2018)
Sexuality is an interesting yet controversial topic in Indonesian culture. The discourse of morality makes it taboo in public. In patriarchy culture, women are always placed as an object of sexuality. In Islam, it also becomes an important topic discussed in Alquran. Now the phenomenon of sex exploitation spreads through the oppression of women’s body. The capitalist uses it to construct a discourse of women’s beauty, to exploit women’s body, and to use seduction to obtain some profits. One of the examples is sales promotion girl (SPG) phenomenon. This reality has influenced some novelists to raise this theme as their main novel topic. One of them is Indah Hanaco. This paper reveals the representation of women’s sexuality in Indah Hanaco’s novel entitled “The Curse of Beauty”. Indah Hanaco had been influenced by the phenomenon of SPG surroundings. Many SPG had trapped in prostitute caused by their sociality lifestyle constructed by the capitalist. They were forced to sell their body to get money to beautify their appearance. It became very important because it was an asset for them. Actually, it was not only about economic motif, but also psychological motif which affected their consciousness. This phenomenon was also widely discussed from the Islamic perspective, especially in the Alqur’an.